Waterborne Acrylic Resin Containing Luminescent Eu3+ Pigments for Luminescent Solar Concentrators. Issue 5 (7th December 2022) - Bertozzi, Andrea Fausto; Picchi, Alberto; Pucci, Andrea
Abstract: This study reports the use of waterborne acrylic resin as a polymer matrix for thin‐film luminescent solar concentrators (LSC). A water dispersable lanthanide complex based on commercially available Eu 3+ chelate (Lumilux SDP Red, Lu Red) is utilized as the red‐emitting pigment. The derived thin polymer films of about 100 µm show absorptions of the organic ligand comprised between 300 and 400 nm, flanked by scattering phenomena caused by the presence of the micro‐sized pigment particles, whose dispersion is not adversely affected by concentration. The film's emission displays the typical fluorescence of Eu 3+ chelates around 600 nm with quantum yields between 20 and 36%. External quantum efficiencies ( η ext ) are found to increase up to 4–4.5% with Lu Red content less than 10–15%, while dropping to about 3% at the highest content, possibly due to the adverse influence of the scattering phenomena within the waveguide. Maximum device efficiencies ( η dev ) of 0.70% confirm the potentiality offered by the new LSC systems, thus definitely supporting the waterborne polymer matrices for the development of high‐performance and water‐based solar collectors. Abstract : Eu(III) chelate pigment mixed with waterborne acrylic resins are found to be accessible solutions for the preparation of water‐based luminescent solar concentrators with performances comparable to those gathered from traditional solar collectors.